PENGARUH DAN DAMPAK STANDARISASI ORDE BARU DALAM ARENA SASTRA DI SUMATRA BARAT DI ERA REFORMASI - Romi Zarman (Universitas Islam Negeri Imam Bonjol Padang, 2014)
Indonesian literature in West Sumatra in the New Order era was centralized in order to maintain uniformity ofthe New Order to preserves the power. Some writers in West Sumatra, including A.A. Navis and Darman Moenir,took a role as agents of the centrality and uniformity in offering a particular standard for the writers, literary critics,and literary history in West Sumatra. This paper examines how the influence and impact on the standardizationof the literary critics, writers, and literary history in the area of West Sumatera in the Reformation era. This paperimplicitly uses Bourdieu's sociological theory, using primary sources of essays, notes, articles, and other forms. Thisstudy reveals that there have been number of attempts aiming to deconstruct standarization designed by the previousregime. However, those attempts were widely seen as attempts to destabilize situation in this area.